Impact of a switch to immediate release on the patient viewing of diagnostic test results in an online portal at an academic medical center - Kelly E. Wood; Hanh T. Pham; Knute D. Carter; Kenneth G. Nepple; James M. Blum; Matthew D. Krasowski (Journal of Pathology Informatics, 2023)
Patient portals allow patients to access their personal health information. The 21st Century Cures Act in the United States sought to eliminate ‘information blocking’, requiring timely release upon request of electronic health information including diagnostic test results. Some health systems, including the one in the present study, chose a systematic switch to immediate release of all or nearly all diagnostic test results to patient portals as part of compliance with the Cures Act. Our primary objective was to study changes in the time to view test results by patients before and after implementation of Cures Act-related changes. This retrospective pre-post study included data from two 10-month time periods before and after implementation of Cures Act-related changes at an academic medical center. The study included all patients (adult and pediatric) with diagnostic testing (laboratory and imaging) performed in the outpatient, inpatient, or emergency department settings. Between February 9, 2020 and December 9, 2021, there was a total of 3 809 397 diagnostic tests from 204 605 unique patients (3 320 423 tests for adult patients; 488 974 for pediatric patients). Overall, 56.5% (115 627) of patients were female, 84.1% (172 048) white, and 96.5% (197 517) preferred English as primary language. The odds of viewing test results within 1 and 30 days after portal release increased monthly throughout both time periods before and after the Cures Act for all patients. The rate of increase was significantly higher after implementation only in the subgroup of tests belonging to adult patients with active MyChart accounts. Immediate release shifted a higher proportion of result/report release to weekends (3.2% pre-Cures vs 15.3% post-Cures), although patient viewing patterns by day of week and time of day were similar before and after immediate release changes. The switch to immediate release of diagnostic test results to the patient portal resulted in a higher fraction of results viewed within 1 day across outpatient, inpatient, and emergency department settings.